STATISTICAL ANALYSIS OF TAX PAYMENTS IN THE SOUTHERN FEDERAL DISTRICT - Igor Yu. Pelevin (Статистика и экономика, 2016)
Foreign tax administration includes the collection of local tax only. The article represents international experience of local tax administration based on this principal.